Pola Pembinaan Keagamaan bagi Lansia pada Panti Jompo Sabai Nan Aluih Sicincin - Andrianto, Andrianto; Saputra, Edriagus; Fata, Azamel; Syamsurizal, Syamsurizal (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research is a field research using a qualitative-descriptive methodology. This study aims to explore the pattern of religious development for the elderly who are in the Panti Sabai Nan Aluih Sicincin, Padang Pariaman Regency. The research results were obtained through observation, interviews and documentation related to the research discussed. The data that has been obtained, then analyzed and presented and narrated in the form of a sentence, paragraph, table, graph and so on. After the data is presented, conclusions will be drawn from the data, making it easier to understand related to the data that has been obtained. From the results of this research, the pattern of fostering the elderly carried out by Panti Sabai Nan Aluih Sicincin, Padang Pariaman Regency is divided into two parts, namely first, coaching in worship. In this coaching, it focuses more on three things, namely the obligation to perform congregational prayers, attend the recitation of the ta'lim assembly and guidance in reading the Qur'an. Second, coaching in the field of morals, which emphasizes mutual respect, maintaining cleanliness, avoiding dirty words, avoiding fights, telling the truth and so on. In the implementation of the guidance, those who violate will be subject to sanctions in the form of a CC trial, a letter of agreement and a reduction in the amount of pocket money. With these sanctions, the elderly have a sense of deterrence, so that these actions are not repeated again.